Determinan Perilaku Kepatuhan Minum Obat Diabetes Mellitus Tipe 2 di Puskesmas Binuangeun Tahun 2025 - M. Sobri Hermawan; Soekidjo Notoatmodjo; Samingan Samingan; Sudibyo Alimoeso (LPPM Universitas Respati Indonesia, 2026)
Diabetes Mellitus Type 2 is a chronic disease whose prevalence continues to increase both globally, nationally, and locally. One of the main challenges in managing this disease is medication adherence. At the Binuangeun Health Center, efforts to improve adherence have been carried out through various programs such as Prolanis, but its effectiveness has not been evenly distributed, especially in non BPJS patients. This study aims to study and explain medication adherence behavior and the factors that influence it in Type 2 Diabetes Mellitus patients at the Binuangeun Health Center, Lebak Regency in 2025. This study uses a quantitative approach with a cross-sectional design. The population is patients with type 2 diabetes mellitus who visited the Binuangeun Health Center in March 2025 totaling 106 people. The sample was taken using a simple random sampling technique with a total of 84 respondents. Data collection was carried out using a structured questionnaire from independent variables, namely determinants such as age, gender, education, occupation, duration of suffering, complications, knowledge, motivation, beliefs, attitudes, perceptions, access to services, family support and health worker support. The dependent variable, namely medication adherence, was measured by the MMAS-8 questionnaire, observation and confirmation from people closest to them. Data will be processed univariately, bivariately with chi-square and multivariate with multiple logistic regression. The results of the study showed a relationship between all independent variables with the behavior of adherence to taking type 2 diabetes mellitus medication at the Binuangeun Health Center in 2025. The most dominant variable was motivation. This study is expected to provide a comprehensive picture of the fulfillment of taking medication in patients with Type 2 Diabetes Mellitus factors and factors that influence it, as a basis for developing more effective and inclusive interventions in managing this disease